2019
DOI: 10.1038/s41598-019-49511-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between Galectin-3 levels within central and peripheral venous blood, and adverse left ventricular remodelling after first acute myocardial infarction

Abstract: Our study investigates association between Galectin-3 levels and adverse left ventricular remodelling (LVR) at six months. Fifty-seven patients following first acute myocardial infarction (AMI) were enrolled in this study and blood samples collected on day 1 from the femoral vein and artery, the right atrium near the coronary sinus and the aortic root, and on day 30, from the cubital vein. Patients with LVESV ≥20% at six months, were included in the LVR group. On day 1, Galectin-3 plasma levels in the femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
(42 reference statements)
2
15
0
Order By: Relevance
“…Therefore, it can be concluded that the values of galectin-3 on day 30 might be more relevant for the prognosis of morbidity (and probably mortality) than those on days 1 and 5. This is consistent with results of our previous study which showed that blood concentration of galectin-3 on day 30 was significant for the observed ventricular remodeling after 6 months [62]. However, further research on a larger study population is needed to monitor the outcome over a longer period of time.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it can be concluded that the values of galectin-3 on day 30 might be more relevant for the prognosis of morbidity (and probably mortality) than those on days 1 and 5. This is consistent with results of our previous study which showed that blood concentration of galectin-3 on day 30 was significant for the observed ventricular remodeling after 6 months [62]. However, further research on a larger study population is needed to monitor the outcome over a longer period of time.…”
Section: Discussionsupporting
confidence: 92%
“…Another study assessed galectin 3 plasma levels in STEMI patients as a predictor of remodeling, defining remodeling as 20% increase in ESV from baseline in a 6-month period. Using these criteria, the incidence of remodeling was 38.6%, which is very similair to our study 20 . Also, in a study by Park et al, which included 50 patients with anterior-wall acute myocardial infarction to test whether longitudinal strain could be a useful predictor of left ventricular remodeling after reperfusion therapy in acute myocardial infarction, a 15% increase in end-diastolic diameter was used to define pathologic remodeling 21 .…”
Section: Discussionsupporting
confidence: 73%
“…Following AMI, inflammatory cells including macrophages, monocytes, and neutrophils migrate to the infarcted myocardium to induce repair. However, the resulting inflammatory response may persist for longer than necessary and lead to further cardiac damage [ 139 ]. MSCs can potentially protect the myocardium following AMI by suppressing persistent inflammation, stimulating angiogenesis and the differentiation of fibroblasts within the infarcted region, abrogating apoptosis, and alleviating fibrosis, hence repairing the myocardium and likely preventing further cardiac dysfunction or heart failure [ 138 ].…”
Section: Extracellular Vesicles From Mesenchymal Stem Cells For Thmentioning
confidence: 99%